A aversão à matemática no olhar dos professores licenciados da rede municipal de ensino de Foz do Iguaçu/PR - Medeiros, Jocineia (2019)
As a social construct, the image of the mathematics discipline is assumed to be difficult, boring, aversive, and other stereotypes denoting negative feelings. And nurturing these kinds of feelings contributes to increasing the problems of teaching and learning Mathematics. Therefore, this investigation aimed to know what polyvalent teachers with degrees in Mathematics think, who work in the Early Years of Elementary Education in the Public Education Network of the municipality of Foz do Iguassu / PR, as to the students' aversion to Mathematics and the influence on the teaching and learning process, having participated in the same 20 (twenty) teachers. The research was exploratory, and was based on a bibliographic and documentary survey, in addition to a questionnaire designed to serve as a data collection instrument. For the data analysis methodology, a qualitative approach based on the Discursive Textual Analysis technique was used. From the analysis, the main theme Aversion to Mathematics emerged, followed by the secondary themes Mathematics is Difficult, Causes and Coping. Among other research results, the main one showed that teachers recognize that the aversion to Mathematics happens in the Early Years of Elementary School,and the students usually arrive at school enjoying this discipline, however, this liking gradually decreases as the level of complexity of the contents increases as the years progress. It was observed that the initial moment of disliking Mathematics is between the 3rd and 4th years, comprising the last year of literacy. The study proves to be very relevant for contributing to the debate on the aversion to Mathematics, in addition to offering information and presenting reflections on the teaching processes in the Early Years of Elementary Education, through the polyvalent teachers who are graduated in Mathematics.